Representasi Keanekaragaman Perempuan Indonesia dalam Produk Kosmetik Lokal - Wiraputra, Ardina Lukita; Pristica, Bela (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
This article explores the representation of diversity among Indonesian women in local cosmetics products within the framework of "social change & culture studies." Employing Cultural Studies, the research analyzes the role of institutions, particularly the beauty industry, in shaping beauty norms in Indonesian society. Simultaneously, the Critical Race Theory approach is utilized to identify and uncover hidden biases, racism, and prejudices within beauty communication. The study aims to achieve social justice by addressing discrimination in beauty representations, providing a deeper understanding of how communication can act as an agent of social change in the context of women's diversity in Indonesia.